hl īqdm ālqrāʾān mbādīʾ tāʾsīsīa lāʾḫlāq bīīʾīaARABICSEMICOLON? = Does the Qurʾān Offer Foundational Principles for Environmental Ethics? - Ḥalalī, ʿAbd-ar-Raḥmān (Journal of Islamic ethics, 2025)
This article tries to answer the question: What principles can be extracted from the Qurʾān to establish environmental ethics? Can it provide a foundation for shaping an Islamic perspective on environmental concerns? The study identifies four religiously-rooted principles that underpin environmental contemplation. The first is the human recognition of the limits of their knowledge compared to the encompassing knowledge of God (faith in the unseen). This doctrinal acknowledgment serves as the religious gateway to the human relationship with nature and the universe. The second principle concerns the concept of harnessing, signifying that the benefits of harnessed resources are viable only within the confines of the established system and plan. Any deviation from this framework fails to fulfill the intended purpose for which these resources were harnessed. The third principle underscores the relationship that God has ordained between humanity, nature, and the Creator, emphasizing their subservience to the Creator. It stresses that human interaction with nature is intrinsically linked to their relationship with Sharīʿa. The fourth principle advocates for balanced and non-excessive utilization of harnessed resources. Collectively, these four principles define the concept of trust as a fundamental moral concept, implying that humanity bears responsibility for averting corruption (aggression against nature) and bloodshed (aggression against Sharīʿa) in this land.